Well-being and mobility of female-heads of households in a fishing village in South India. Issue 5 (4th May 2021) - Azmi, Fazeeha; Lund, Ragnhild; Rao, Nitya; Manimohan, R.
Abstract: This paper focuses on how Female Heads of Households (FHHs) in a village in Cuddalore District, in the state of Tamil Nadu, India, have tried to achieve their various well-being targets and overcome their vulnerabilities through engaging in fish trading and auctioning that in turn involves moving within and outside their village. The study is based on a three-week fieldwork undertaken in April and May 2017, including multiple methods, such as observations, village walks, informal discussions, focus group discussions, and in-depth interviews. We address how FHHs' well-being intersects with old vulnerabilities that are an inherent part of their fishing culture (caste, class and gender) and new vulnerabilities created due to precarities related to mechanized fishing, modernization and post-tsunami development. We found that the complex situation of vulnerability and precarity in the fishing sector have affected the material, relational, and subjective well-being of FHHs differently, benefitting some female auctioneers but not the majority of fish vendors. In particular, the mobility of younger FHHs was restricted due to familial and social expectations.